Epistemologi Tafsir Indonesia: Kajian Epistemologi Penafsiran Q.S. Al-Falaq [113]: 3-4 dalam Tafsir Al-Azhar Karya Hamka - Wendi Parwanto (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
Ideally, interpretations written by Indonesian mufassir tend to display Indonesian locality. Therefore, this paper will explain the existence of the locality and historicity of Hamka when interpreting Qs. Al-Falaq [113]: 3-4. This type of study is a literature review with a descriptive-analytic method and uses the theory of epistemology. The formal object of study uses the interpretation of al-Azhar, as well as the material object is the interpretation of Qs. Al-Falaq [113]: 3-4. The conclusion of this article explains that: First, the epistemology of interpretation of Qs. Al-Falaq [113]: 3-4, sources of interpretation using munasabah, hadith, scholars' opinions, and ra'yu (reason). Interpretation methodology: Tahlili (analysis/detail), contextual approach, with the style of al-Adab wa-al-Ijtima'i (socio-cultural). The validity of coherent interpretation is coherent with the interpretation of the previous verse, that is, they both reveal illustrations. Pragmatically, according to the reality of the community, especially the community as an audience and target in da'wah activities.